2003
DOI: 10.1177/147059310333003
|View full text |Cite
|
Sign up to set email alerts
|

The Harm Chain

Abstract: This paper introduces the concept of a 'harm chain' as a mechanism to further broaden the way in which firms and public policy makers consider potential negative outcomes from marketing activities. The purpose of conceptualizing a 'harm chain' is to examine specifically the creation of harm within networks of marketing exchanges that might occur throughout preproduction, production, consumption and post-consumption activities. The authors suggest that addressing issues where harm occurs allows both firms and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(13 citation statements)
references
References 52 publications
0
12
0
1
Order By: Relevance
“…Marketing studies have traditionally focused on consumers and competitors; however, they have increasingly recognized that firms need to consider a broader range of stakeholders to be successful (Evers et al, 2012;Freeman, 1984;Polonsky et al, 1999). There are different views about which groups or actors a firm should consider as stakeholder (Frow and Payne, 2011;Polonsky et al, 2003). However, we maintain to a definition based on Donaldson and Preston (1995, p. 67): "Stakeholders are persons or groups with legitimate interests in procedural and/or substantive aspects of corporate activity".…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Marketing studies have traditionally focused on consumers and competitors; however, they have increasingly recognized that firms need to consider a broader range of stakeholders to be successful (Evers et al, 2012;Freeman, 1984;Polonsky et al, 1999). There are different views about which groups or actors a firm should consider as stakeholder (Frow and Payne, 2011;Polonsky et al, 2003). However, we maintain to a definition based on Donaldson and Preston (1995, p. 67): "Stakeholders are persons or groups with legitimate interests in procedural and/or substantive aspects of corporate activity".…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Polonsky, 1996). For example, in introducing the concept of the 'harm chain', Polonsky, Carlson and Fry (2003) apply a stakeholder management approach to interrogate the harms that can arise from marketing exchanges.…”
Section: Broadening and Deepening The Social Marketing Fieldmentioning
confidence: 99%
“…Ackermann & Eden, 2011;Bryson, 2004;Freeman, 1984) and, to a lesser extent, from applications in marketing (e.g. Polonsky et al, 2003). This literature classifies the challenges arising when managing such stakeholders into a number of broad areas: namely, the need to identify who the specific stakeholders are, the importance of understanding the dynamics occurring between these stakeholders, and the need for stakeholder management strategies that aid the management of the relationships.…”
Section: Broadening and Deepening The Social Marketing Fieldmentioning
confidence: 99%
“…Besides the above-mentioned transformations in marketing thought, consequential events, such as the Great Recession, climate change, and the yellow vests movements as well as the soul-draining practices of positive marketing demonstrated that marketing discipline has a duty to transform itself beyond dominant positivist managerial epistemology. Polonsky et al's [40] "harm chain" acknowledges how transactional activities result in the generation of harm. Today, the "received marketing paradigm" is in the grip of disintegration since laisses-faire capitalism no longer seems to be sustainable [11].…”
Section: Transformation Of Value In Marketing: From Value Maximizatiomentioning
confidence: 99%